Dalla Castiglia al Cile, e ritorno: terre, uomini e costumi in Un novelista descubre América (1956) e Diario de un emigrante (1958) di Miguel Delibes - Londero, Renata (Oltreoceano - Rivista sulle migrazioni, 2021)
Nel presente lavoro si analizzano le concomitanze tematiche, strutturali e linguistiche tra l’originale romanzo autobiografico – costruito sulla linea del diario intimo – Diario de un emigrante (1958) e gli articoli giornalistici raccolti in Un novelista descubre América (1956). From Castile to Chile and Back: Lands, Men and Customs in Delibes’ Un novelista descubre América (1956) and Diario de un emigrante (1958) This article analyzes the thematic, structural and linguistic analogies between two interesting works by the Spanish contemporary writer Miguel Delibes dealing with Chile: the novel Diario de un emigrante (1958) and the collection of journalistic articles Un novelista descubre América (1956).